Odontogenic Myxoma in Children: A Case Report and Literature Review - Dalbo Contrera Toro, Mariana (Case Rep Oncol Med, 2016)
Benign odontogenic lesions are rare entities but are very important due to their locally aggressive nature. Odontogenic myxoma is even rarer in children than in adults. There is no evidence in the literature in regard to the best treatment approach, in terms of conservative or aggressive surgery, for this type of tumor. This paper reports a case of odontogenic myxoma in a child treated with a compromised approach through bone osteotomies and a review of the literature about this disease, especially in pediatric patients.